Analisis Pendidikan Karakter Pada Pembelajaran Matematika Materi Nilai Mutlak Siswa Di SMA Kelas X Harapan Bangsa Samalantan - Derisius Yongki; Yadi Ardiawan; Rahman Haryadi (International Forum of Researchers and Lecturers, 2023)
The importance of character education in learning is to improve the quality of implementation and educational outcomes in schools which leads to the achievement of student character formation. In this case, the teacher is not only tasked with delivering learning material, but is also tasked with instilling character values in students (Fatmawati, 2017: 8). This type of research is qualitative research and the method used is a descriptive method. Sugiyono (2017:9) qualitative research is a research method used to examine natural objects. The main aim of qualitative research is to understand social phenomena or symptoms by providing an explanation in the form of a clear description of the social phenomenon or symptom in the form of a series of words which will ultimately produce a theory, which is explained (Sujardewi, 2014: 110). Based on the description that has been presented, this research is defined as a research process that produces descriptive data in the form of written or spoken words from people and behavior that is observed and carried out naturally. This research uses a qualitative research method with the hope of being able to describe the analysis of character education in mathematics learning material on absolute values for students at SMA class X Harapan Bangsa Samalantan. absolutely at SMA Harapan Bangsa Samalantan class X. In chapter IV, the results of the research that has been carried out and the discussion are presented. Therefore, (1) Results, (2) Discussion are successively put forward.1. Analysis of character education in mathematics learning with absolute value material in class X has been carried out by the teacher through planning, implementation and evaluation carried out by the teacher. Mathematics teachers in planning mathematics learning material have absolute values for the character values listed in the RPP, namely the character values of discipline, honesty, responsibility and skills. In implementing learning, mathematics teachers also apply character education through methods, strategies and learning media. Analysis of character education in mathematics learning with absolute value material is based on lesson plans that have been created and adapted to learning conditions. The teacher's learning implementation uses the case study method, so that students always think critically in their efforts to solve problem formulation in mathematics learning with absolute value material. Assessment of the achievement of character education in mathematics learning absolute value material in class X using test questions and observation sheets of student behavior in learning.